2012
DOI: 10.1161/circulationaha.111.088807
|View full text |Cite
|
Sign up to set email alerts
|

Post–Cardiac Arrest Mortality Is Declining

Abstract: Background— Despite several advances in postresuscitation care over the past decade, population-based mortality rates for patients hospitalized with cardiac arrest in the United States have not been studied over this time period. The aim of this study was to determine the annual in-hospital mortality rates of patients with cardiac arrest from 2001 to 2009. Methods and Results— The US mortality rates for hospitalized patients with cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(74 citation statements)
references
References 16 publications
7
66
0
1
Order By: Relevance
“…Large administrative databases such as the NIS are lacking readmission status and cause of death and are prone to coding errors. There can be misinterpretation of procedure volumes and underreporting of comorbid conditions 23, 35. We have identified prevalence of cardiovascular manifestations in sarcoidosis by presence of concurrent diagnosis codes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large administrative databases such as the NIS are lacking readmission status and cause of death and are prone to coding errors. There can be misinterpretation of procedure volumes and underreporting of comorbid conditions 23, 35. We have identified prevalence of cardiovascular manifestations in sarcoidosis by presence of concurrent diagnosis codes.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities used in our study were derived from Elixhauser method for quantification of comorbidities 14. A cardiac arrest ( ICD‐9‐CM diagnosis code 427.5) was identified from the disease class of arrhythmias 23. We identified all discharges who came or required new ICD implantation or replacement while hospitalized ( ICD‐9‐CM procedure codes‐37.94, 37.95, and 37.96), CRT implantation or replacement ( ICD‐9‐CM procedural code‐00.50, 00.51), or PPM implantation ( ICD‐9‐CM procedural code‐37.7, 37.8) by using primary and secondary procedural fields.…”
Section: Methodsmentioning
confidence: 99%
“…The survival rate of OHCA victims remained low until the early 2000s. 4 However, the past 10 years have witnessed the advancement of OHCA studies using large data, which have shown drastic improvement in OHCA survival rates in locations globally, including the USA, 5 Europe, 6,7 and Asia. [8][9][10][11] Large-scale studies have suggested that two factors are key to achieving improvement: bystanders' actions in prehospital settings, 3,[6][7][8][9]12,13 and postresuscitation care following hospital arrival.…”
mentioning
confidence: 99%
“…[8][9][10][11] Large-scale studies have suggested that two factors are key to achieving improvement: bystanders' actions in prehospital settings, 3,[6][7][8][9]12,13 and postresuscitation care following hospital arrival. 5,10,14 However, the majority of the evidence presented in these studies was derived from either pre-or in-hospital databases. Therefore, simultaneously assessing both the bystanders' actions in prehospital settings and postresuscitation care in hospital was infeasible.…”
mentioning
confidence: 99%
“…Approximately half of the patients in the TTM trial survived, the large majority with a good neurological outcome at 180 days, evaluated with rather crude but established outcome measures during a face-to face follow-up. In-hospital mortality among patients admitted alive after out-of-hospital cardiac arrest thus remains high, although a doubling of in-hospital survival has been described in the last decade [9] thanks to the introduction of post-cardiac arrest care bundles including controlled temperature, angiography, improved ICU-care in general and possibly increased enthusiasm for the patient group.…”
mentioning
confidence: 99%